2019
DOI: 10.15625/1859-3097/19/4a/14595
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the variability of upwelling system in the South Central Vietnam waters under the impact of ENSO events and its impact on hydrographic conditions of the Ninh Thuan-Binh Thuan waters

Abstract: In this paper, we have exploited and analyzed data from HYCOM + NCODA Global 1/12.5o Reanalysis database in the period of 20 years from 1993 to 2012 and from 2013–8/2016 for the data assimilation of the HYCOM + NCODA Global 1/12° Reanalysis - for 22 depth layers in the East Sea area. The research results show that there are changes in the upwelling phenomenon and hydrological structure in the Ninh Thuan - Binh Thuan waters under the influence of ENSO phenomenon as follows: La Niña can degrade and eliminate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…However, in July 2016, the upwelling phenomenon appeared with the centre moving closer to the shore than in normal years. The offshore area of Ninh Thuan -Khanh Hoa was strongly affected by upwelling [27]. When upwelling water is active, cold deep water layers move vertically to the surface, reducing sea surface temperature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in July 2016, the upwelling phenomenon appeared with the centre moving closer to the shore than in normal years. The offshore area of Ninh Thuan -Khanh Hoa was strongly affected by upwelling [27]. When upwelling water is active, cold deep water layers move vertically to the surface, reducing sea surface temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Research on the upwelling water system in the South Central Coast shows that in June-July 2010, there was a decrease in long-shore currents in the north-northwest direction from the north of Ninh Thuan to the sea of Binh Dinh. This current system eliminated the anti-cyclonic vortex off the coast of Ninh Thuan -Binh Thuan, causing the upwelling phenomenon to be eliminated in 2010 [27]. Thus, due to the combined effect of the increase in SST (above 30 o C) and the suppression of the upwelling phenomenon, coral bleaching in Khanh Hoa coastal area in 2010.…”
Section: Discussionmentioning
confidence: 99%
“…In Vietnam, there have been many studies related to the ENSO phenomenon so far. The studies on the variability of the upwelling system in the South-Central Vietnam waters under ENSO events and its impact on hydrographic conditions of the Ninh Thuan-Binh Thuan waters [18] have shown that the La Niña events can degrade and eliminate the upwelling phenomenon. The study of abnormal features of oceanographic characteristics in upwelling Vietnam waters under the influence of El Niño events [19] has partly clarified the impact of the El-Niño phenomenon on the occurrence time and position of the center region of the Vietnam upwelling waters.…”
Section: Introductionmentioning
confidence: 99%